Case Study on Earnings Management of Listed Companies in China - Ben Fang (Randwick International of Social Science Journal, 2024)
Earnings management of listed companies is a key issue in the study of business behavior. Although the research on earnings management has been going on for a long time, with the development of market economy, various problems that are not conducive to corporate profits are likely to occur in the operation of enterprises. For the purpose of avoiding delisting and other purposes, the management of enterprises will carry out earnings management by various means within the scope permitted by accounting standards to maximize profits. Under the background of market economy, the study of earnings management is of great significance to standardize the behavior of listed companies and promote the healthy development of economy. Based on the case of earnings management of YC Technology Co., Ltd., a listed company in China, this paper makes an in-depth analysis of earnings management from the aspects of motivation, means and impact by studying the annual report of the company, and provides reasonable suggestions for improving the company's profitability and promoting economic quality and efficiency.